Positron-lifetime studies of defected solids - Mäkinen, Seppo (1991)
This thesis reviews the main results of seven publications in which the positron lifetime technique has been used to identify and to study the annealing kinetics of different kinds of lattice defects in crystalline materials. In the first paper we build the basis for theoretical positron state calculations and study the screening of positrons in non-metallic materials. Two new models are developed for representing the pile-up of valence electrons around the positron in semiconductors and insulators. By using these models we calculate the positron lifetimes in most of the known semiconductors and insulators. We also estimate the positron lifetimes corresponding to the non-relaxed and neutral vacancies in these materials. In the second paper we use the screening models for semiconductors and metals and study the nature of the screening of positrons in some vacancy-impurity pairs in semiconductors. The lattice relaxation and the vacancy charge state are included in these calculations. In the subsequent two papers we calculate positron states at dislocation lines and loops in Al and Cu, and also at a vacancy and a jog associated to a dislocation line. We show that a pure dislocation line is a very weak positron trap, and that a vacancy-type defect in the dislocation core is needed for strong positron trapping. In the fifth and sixth paper we present low-temperature positron lifetime studies of proton-irradiated, and H⁺- and ³He²⁺-implanted single-crystal Si. We can identify the types and charge states of the induced point defects, and show that the positron trapping rate varies as T⁻⁰·⁵ for the negatively charged vacancy-type defects. In the last paper we show evidence of positron self-trapping in a perfect crystalline material, Nd₂ Fe₁₄B. Both experimental and theoretical studies have been made to study this phenomenon.